2007
DOI: 10.1128/mcb.00944-06
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Recruitment of Histone Methyltransferase G9a and Other Chromatin-Modifying Enzymes in SHP-Mediated Regulation of Hepatic Bile Acid Metabolism

Abstract: SHP has been implicated as a pleiotropic regulator of diverse biological functions by its ability to inhibit numerous nuclear receptors. Recently, we reported that SHP inhibits transcription of CYP7A1, a key gene in bile acid biosynthesis, by recruiting histone deacetylases (HDACs) and a Swi/Snf-Brm complex. To further delineate the mechanism of this inhibition, we have examined whether methylation of histones is also involved and whether a functional interplay between chromatin-modifying enzymes occurs. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
124
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(131 citation statements)
references
References 52 publications
(129 reference statements)
7
124
0
Order By: Relevance
“…The primary basis for this effect is the induction of SHP by FXR in the presence of elevated bile acid levels, inhibiting transactivation by the nuclear receptors liver receptor homolog-1 (LRH-1) and possibly hepatocyte nuclear factor 4 alpha (HNF4ā£) and repressing expression of Cyp7A1, the rate-limiting enzyme of bile acid biosynthesis, as well as a number of other bile acid biosynthetic enzymes. 7,8,[23][24][25] This function of SHP has been strongly supported by results with Shp ĻŖ/ĻŖ mice, which reveal defective repression in response to synthetic FXR agonists 10,11 or very short term dietary bile acid treatment. 26 However, such studies have also demonstrated the importance of SHP-independent pathways that can efficiently repress Cyp7A1 and other negative targets in response to longer term treatments with dietary bile acids.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The primary basis for this effect is the induction of SHP by FXR in the presence of elevated bile acid levels, inhibiting transactivation by the nuclear receptors liver receptor homolog-1 (LRH-1) and possibly hepatocyte nuclear factor 4 alpha (HNF4ā£) and repressing expression of Cyp7A1, the rate-limiting enzyme of bile acid biosynthesis, as well as a number of other bile acid biosynthetic enzymes. 7,8,[23][24][25] This function of SHP has been strongly supported by results with Shp ĻŖ/ĻŖ mice, which reveal defective repression in response to synthetic FXR agonists 10,11 or very short term dietary bile acid treatment. 26 However, such studies have also demonstrated the importance of SHP-independent pathways that can efficiently repress Cyp7A1 and other negative targets in response to longer term treatments with dietary bile acids.…”
Section: Discussionmentioning
confidence: 56%
“…20 It is a transcriptional repressor and exerts its regulatory functions through protein-protein interactions with other nuclear hormone receptors and possibly other transcription factors, which can inhibit or even reverse their transactivation. [20][21][22][23][24][25] Regulation of bile acid metabolism is the most prominent of a number of physiological roles proposed for SHP. The primary basis for this effect is the induction of SHP by FXR in the presence of elevated bile acid levels, inhibiting transactivation by the nuclear receptors liver receptor homolog-1 (LRH-1) and possibly hepatocyte nuclear factor 4 alpha (HNF4ā£) and repressing expression of Cyp7A1, the rate-limiting enzyme of bile acid biosynthesis, as well as a number of other bile acid biosynthetic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…G9a-associated transcription repression might be also involved in the postdevelopmental stage and participate in a short term gene regulation. Indeed, G9a-dependent methyltransferase activity has been found to be involved in the expression of Th2-associated cytokines (27), terminal differentiation of B-lymphocytes (28), bile acid metabolism (29), cocaine-induced neuronal plasticity (30), tumor growth and metastasis (31)(32)(33), and the interferon response (34). No previous studies have reported the role of G9a in lipid metabolism in the liver.…”
mentioning
confidence: 99%
“…A likely explanation for this difference is that SHP recruits other corepressors through the helix H12 site that act independently of EID1. Indeed, previous studies have shown SHP helix H12 is crucial for its repressor activity (24), and EID1 is known to form a multiple-component complex with other corepressors to regulate SHP's inhibitory activity (20,22,23). For this reason, mutation of the SHP-EID1 interface residues F72, L76, and F178 might be expected to compromise both EID1 binding and repression activity, whereas mutations of other SHP-EID1 interface residues may still retain SHP repressor activity because they permit the assembly of other non-EID1-dependent corepressors through the H12 helix.…”
Section: Arillmastlknipgtllvdlffrpimgdvditelledmlllr-aelnsalfllrfinsdmentioning
confidence: 99%
“…In the second step, SHP actively recruits corepressors to inhibit gene transcription. Identification of SHP-interacting corepressors has been a subject of intense study in recent years (19)(20)(21)(22)(23)(24)(25). As a result, a number of proteins have been isolated that bind to SHP in in vitro or in vivo assays, one of which is E1A-like inhibitor of differentiation (EID1) (24).…”
mentioning
confidence: 99%